Estresse, coping, síndrome de burnout, sintomas depressivos e hardiness em docentes de enfermagem - Kirchhof, Raquel Soares (2013)
This research has the objective to relate stress, coping, Burnout Syndrome, depressive symptoms and Hardiness in nursing professors. The hypothesis is that professors with Hardiness personality present low stress is opposed to depressive symptoms and the occurrence of Burnout Syndrome. It is a transversal analytical study with a quantitative approach, developed with 108 (61,36%) nursing professors of Rio Grande do Sul Federal Universities: Santa Maria Federal University, Rio Grande Federal University Foundation, Porto Alegre Federal University of Health Sciences, Rio Grande do Sul Federal University, Pelotas Federal University, Pampa Federal University, Northern Superior Education Center-RS. A compound protocol with an application form was used to collect data. This protocol focused on socio-demographic and professional information, level of stress at work, coping strategies inventory, Maslach Inventory Burnout, Beck depression inventory and Hardiness Scale. The data collection was done between April and June, 2013. The data analysis was developed with the help of the Statistical Package for Social Science software (SPSS, version 17.0), through a descriptive and bivariate statistics. It has been identified 58,33% of professors with Hardiness Personality, 6,48% with high stress, who used coping strategies focused on emotion, such as Social Support . Also 1,85% of the population investigated presented some indication of Burnout Syndrome and 2,78% showed a suggestive indication of depression. Correlating the constructs, it has been verified that professors with Hardiness Personality present significant negative correlation with low stress, depressive symptoms, and the subscales of Burnout. In this sense, the hypothesis of this study can be confirmed. Considering the fact that the Hardiness Personality can be apprehended, it is suggested that the higher education institutions mobilize themselves in order to subsidize the study of this personality and reduce the stressing processes, improving the professors quality of work and life.